FROM DENOTATION TO MYTH: CONSTRUCTING DEATH AND HUMAN MORALITY IN FRIDOLIN UKUR'S THE ONE WHO LEAVES AND THE ONE WHO STAYS - Yulia Sintia Sari; Ayu Setiyo Putri (FKIP Universitas Lampung, 2026)
This study aims to examine the construction of the meanings of death and human morality in Fridolin Ukur's poem The One Who Leaves and The One Who Stays using Roland Barthes' semiotic framework. Employing a qualitative descriptive approach, the study analyzes poetic expressions through three levels of signification: denotation, connotation, and myth. The findings reveal that, at the denotative level, the poem depicts the existential realities of life and death as inseparable dimensions of human existence. At the connotative level, the signs construct meanings associated with life's journey, worldly temptations, spiritual awareness, and moral struggles experienced by human beings. At the mythic level, the poem reproduces cultural and ideological beliefs that portray life as a moral test shaped by material desires, while death is represented as both liberation from worldly suffering and the inevitable consequence of human choices. These findings demonstrate that the poem constructs layered meanings through the interaction of linguistic signs, cultural experiences, and ideological values, thereby presenting a critical reflection on the tension between worldly pursuits and spiritual consciousness. This study contributes to literary semiotics by demonstrating how Barthes' concepts of denotation, connotation, and myth can uncover the ideological dimensions embedded in poetic discourse, particularly in representing death and human morality.